Tardigrades of Kristianstads Vattenrike Biosphere Reserve with description of four new species from Sweden - Massa, Edoardo; Guidetti, Roberto; Cesari, Michele; Rebecchi, Lorena; Jönsson, K. Ingemar (Scientific Reports, 2021)
Kristianstads Vattenrike Biosphere Reserve [KVBR] is a UNESCO designated area of Sweden possessing high biological value. Although several studies on tardigrades inhabiting Sweden have been performed, the KVBR area has been neglected. The current study investigates the tardigrade fauna of five areas of the biosphere reserve and includes 34 samples of different substrates analysed quantitatively and qualitatively. In total, 33 species of tardigrades were found in the samples, including 22 new records for the Skåne region, 15 new records for Sweden, and four species new to science. Mesobiotus emiliae sp. nov., Xerobiotus gretae sp. nov., Itaquascon magnussoni sp. nov., and Thulinius gustavi sp. nov. were described with an integrative approach (when possible) using morphological characters (light, electron scanning, and confocal laser scanning microscopies) and molecular markers (ITS2, 18S, 28S, cox1). A new protocol to increase morphological data was developed recovering mounted specimens within old slides for SEM analysis. Emended diagnoses for the genus Itaquascon and the transfer of Platicrista itaquasconoide to the genus Meplitumen are proposed. This study enriches the knowledge of the tardigrade biodiversity both within the KVBR and in Sweden and contributes to the rapidly increasing number of tardigrade species reported worldwide. The 33 species identified in the KVBR area represents 28% of all water bear species found in Sweden so far. The restricted study areas and limited number of samples collected suggests that the KVBR is very rich of tardigrades.